The Delta variant will cost many lives and some GDP - Steven B. Kamin; John Kearns (American Enterprise Institute (AEI), 2021)
In this note, we gauge the likely impact of the Delta variant on global GDP growth in the second half of this year. To do so, we use the methodology described in Kamin and Kearns (2021), "Pandemic Prospects and the Global Economic Recovery," to compare projections for global GDP based on the IHME's recent forecast of pandemic deaths to GDP projections based on IHME's forecast released before the full eruption of the Delta variant – the difference between them is a rough measure of the economic impact of the Delta variant. Our estimates suggest that although the Delta variant may cost more than 900,000 lives around the world, the impact on global GDP will be a more modest 200 billion, or less than 0.2 percent of GDP. Most of the lives lost to the Delta variant in the second half of this year will be in the emerging market and developing economies (EMDEs), but this reflects their much larger population; adjusted for population, the advanced economies stand to be hit much harder. In fact, much of the human and economic costs of the Delta variant are concentrated in the United States: the country stands to lose 120,000 additional lives and 70 billion in GDP, a testament to the damage being done by vaccine hesitancy. Finally, despite the EMDEs being hit less hard than the AEs by the Delta variant, the pandemic will still cost them nearly 1 million lives and 190 billion in lost GDP in the second half of this year. Thus, the need to provide vaccines to these countries remains as urgent as ever.
Keywords: A; 330; Coronavirus; Global Economy; Gross Domestic Product (GDP); Pandemic; Vaccines